The politics of unemployment in Europe. Policy responses and collective action (Aldershot, 2009)
"This book offers a state-of-the-art discussion of the political issues surrounding unemployment in Europe. Its unique combination offers both a policy and institutional perspective, whilst studying the viewpoint of individual civil society members engaging in collective action on the issue of joblessness. It is the result of Marco Giugni’s three year cross-national comparative research project, financed by the European Commission, united with hand picked contributions from invited experts. Throughout his study he focuses on how the EU approaches national unemployment, the main national differences in talk about unemployment and unemployment policy, and how the representatives of the unemployed produce and coordinate demands in relation to unemployment policy. This book contains a number of genuinely cross-national chapters along with sections on specific national cases, namely the UK, Ireland, Germany, Switzerland, Belgium and Sweden."